Re-examining the Representation of the Land in Hosea 4–11 in Light of Sacred Space - Rembold, Stefanie (Old Testament Essays, 2024)
This article reconsiders the role of land in the YHWH-Israel relationship in Hos 4–11, a text which reworks positive notions of land—gift, inheritance, homeland—as the land becomes associated with Israel’s iniquitous actions and distorted values. To achieve this, the study explores how land is represented as a sacred space in the text and how sacred space is subject to the actions, ideas and perceptions of the people who inhabit the land. The study employs a synchronic, social-scientific approach and conducts a thematic analysis of the text, focusing on the interconnections of sacred space’s moderators—holiness, cultural memory and covenantal exchange—and their place in the land’s deconstruction and reconstruction. Considering these relational modes, the study shows that the representation of the land is reflected in the text’s movements from deconstruction to reconstruction, which suggests that the state of the YHWH-Israel relationship is interlaced with the physical landscape.